Zwischen Innerer Emigration und Exil : deutschsprachige Schriftsteller, 1933-1945 - Gołaszewski, Marcin; Kardach, Magdalena; Krenzlin, Leonore (Schriften der Internationalen Ernst-Wiechert-Gesellschaft, 2016)
"This volume seeks to unite two traditionally divided research areas, "exile literature" and "inner emigration," and to interrelate the divergent experiences of writers who were exiled and writers who remained in Germany. It discusses the potentially resistant nature of German literature both inside and outside the German Reich and examines the relevance of the terms "inner" and "outer" emigration."--